Estrutura de comunidade e padrões de distribuição de macrófitas aquáticas em lagos de duas Unidades de Conservação na Amazônia Central, e implicações para as cadeias tróficas - Guterres-Pazin, Michelle Gil (Botânica, 2025)
The floodplain areas of the Amazon Basin are classified into várzeas, fertile zones flooded by whitewater rivers, and igapós, less fertile, areas inundated by blackwater and clearwater rivers. The flood pulse determines the ecological dynamics and distribution of aquatic macrophytes, which play an essential role in carbon sequestration, nutrient recycling, and supporting fauna. The Amazonian manatee, a species threatened with extinction, feeds on various macrophytes, contributing to the nutrient cycle and primary production in aquatic ecosystems. Its seasonal migration between várzeas and igapós is influenced by water levels, remaining in the várzeas during high water and migrating to the igapós during the dry season. Given the influence of the annual water cycle on floodplain ecosystems, it is vital to understand how abiotic factors affect the dynamics of aquatic macrophyte communities and their implications for the trophic chains of aquatic herbivores, particularly the Amazonian manatee. The general objective of this thesis was, therefore, to document and compare community structure, distribution patterns, and nutritional composition of aquatic macrophytes and their relationship with seasonal abiotic factors in várzea and igapó environments, as well as their implications for trophic chains in two Sustainable Use Conservation Units in Central Amazonia. As results, 64 species of aquatic macrophytes were identified, with 50 species recorded in Lake Mamirauá (várzea) and 45 in Lake Amanã (igapó), 30 of which were shared between both environments. During the flood season, hydrological connectivity with more fertile rivers increased the abundance and dominance of emergent floating macrophytes in the várzea and the initial portion of the igapó, while in the dry season, diversity and abundance decreased due to the lakes' hydromorphometric constraints. Seasonality played an important role in plant community composition, with autogenic processes prevailing during the dry period, favouring the colonisation of emergent macrophytes, albeit with differences between environments. The physical and chemical characteristics of the lakes influenced species richness and abundance across várzea and igapó, with significant differences between ecosystems, showing greater diversity and abundance in the várzea, as well as variations between flood and dry periods. The nutritional composition of the plants did not differ significantly between várzea and igapó environments on an annual basis, but variation within each type of floodplain throughout the hydrological cycle was evident. During the flood and receding water periods, elevated levels of fat and crude fibre in aquatic macrophytes suggest a higher energetic contribution to the manatee during its reproductive and migratory phases. Nevertheless, regardless of season and environment, in years with a regular hydrological cycle, manatees can access aquatic macrophytes to meet their nutritional needs. During an extreme drought event in 2023, on the sandy beaches of Lake Amanã, we identified nine macrophyte seed morphotypes and 79 seedlings of various species growing in manatee faeces, indicating that their migration is synchronised with the fruiting of aquatic macrophytes and the flood pulse, enabling endozoochorous dispersal across different aquatic environments. This behaviour contributes to the dispersal, colonisation, and succession of plants, in addition to fertilising the waters and promoting plant productivity, elevating the manatee to the role of "gardener" of Amazonian wetlands. The results of this research highlight the importance of the flood pulse and hydrological connectivity in regulating aquatic macrophyte communities and the seasonal migration of the manatee, providing essential information for the conservation of wetlands in the face of climate change and human pressures.
Keywords: Ecologia de macrófitas aquáticas; Interação planta-animal; Dispersão endozoocórica; Trichechus inunguis